Localization Of Multiple Harmonic Sources For Inverter Loads Utilizing Periodogram - Jopri, Mohd Hatta; Abdullah, Abdul Rahim; Nabilah , Mat Kassim; Manap, Mustafa; Ngatiman, Nor Azazi; Yusoff, Mohd Rahimi (Penerbit Universiti, UTeM, 2016)
-